Graphene-based multifunctional surface and structure gradients engineered by atmospheric plasma - Fiasal K.Alosaimi (Elsevier, 2022)
Surface and structure gradients are ubiquitous in nature, where gradual changes in physical, chemical, mechanical and other properties of biomaterial are generated aiming to achieve intricate biological functions. These bioinspired gradients have been explored and fabricated using different materials in small scales (nm or µm) and usually with single function. Leveraging an outstanding property of graphene and their multi functionality, this paper presents a demonstration of the surface and structure gradients with gradual change of multiple functionalities such as structure, chemistry, wettability, charge, electrical and thermal conductivity in all three dimensions (1D, 2D and 3D).